In situ preparation of Bi2O2Se/MoO3 thin-film heterojunction array flexible photodetectors. Issue 41 (29th September 2022) - Yang, Ming; Zhang, Xiaoqiang; Zhou, Hongxi; Fu, Gui; Zhou, Xin; Lian, Yunlun; Hao, Jinxin; Yu, He; Zhu, Xinyu; Wang, Jun
Abstract : The Bi2 O2 Se/MoO3 heterojunction has the characteristics of high stability and detection in the optical communication spectrum, which provides a simple and effective method to fabricate large-scale, fast response, broadband flexible array optoelectronic devices. Abstract : Bi2 O2 Se has broad applications in optoelectronics and electronics because of its excellent air stability and electron mobility. Bi2 O2 Se is a promising candidate for high-performance infrared (IR) applications. However, very few studies on Bi2 O2 Se-based IR devices have been reported so far. Here we developed a Bi2 O2 Se/MoO3 thin-film heterojunction photodetector in the broadband range of 405–1550 nm that exhibits a fast-response time, and ultrahigh specific responsivity ( R i ), detectivity ( D *), and on/off ratio. The device showed excellent long-term stability (>90 days) without any protective measures under environmental conditions. Furthermore, the prepared Bi2 O2 Se thin film showed no selectivity for the substrate, making it a promising candidate for preparing CMOS-compatible and flexible devices. The device exhibited great flexibility, and the performance was decreased by only 7.17% after bending by 39% and remained unchanged for 1000 cycles. The device's excellent photoelectric properties suggest that the Bi2 O2 Se/inorganic heterojunction is a promising way for the fabrication of high-efficiency optoelectronic devices for remote sensing, imaging, and military applications.